The Effect of Cultivation of Medicinal Plants on Job Creation in Rural Areas: (Case Study: Villages of Kalat City) - Mansoureh Alipourkhasht, Dr. Hamid Jafari, Dr. Katayoun Alizadeh (International Journal of Modern Agriculture, 2021)
The diversity of economic activities creates a kind of security for the villagers, so that if one of the crops is damaged as a result of weather disasters or the spread of pests, the villagers' economy is not completely endangered and the other crop Â¬ can guarantee the minimum possible for them, therefore the production of medicinal plants and can be a national necessity, within a clear and comprehensive program, pharmaceutical self-sufficiency, employment and development of the agricultural sector and pursue in Currency exchange is effective for the country. The aim of this study was to investigate the effect of cultivation of medicinal plants on job creation in rural areas (case study of villages in Kalat city). The present study is applied in terms of purpose and descriptive-analytical in terms of method. The sample population includes 7 villages of Kalat city in which medicinal plants are produced. According to the research results, planting each hectare of medicinal plants creates an average of 103.1% more jobs compared to crop heads.